2016
DOI: 10.3390/su8101045
|View full text |Cite
|
Sign up to set email alerts
|

Simulating the Impact of Economic and Environmental Strategies on Future Urban Growth Scenarios in Ningbo, China

Abstract: Coastal cities in China are challenged by multiple growth paths and strategies related to demands in the housing market, economic growth and eco-system protection. This paper examines the effects of conflicting strategies between economic growth and environmental protection on future urban scenarios in Ningbo, China, through logistic-regression-based cellular automata (termed LogCA) modeling. The LogCA model is calibrated based on the observed urban patterns in 1990 and 2015, and applied to simulate four futur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 61 publications
0
25
0
Order By: Relevance
“…The different levels of economic development and different household structures in different regions often cause very different travel behavior [26,27]. In addition, most of the above studies are only a descriptive analysis and lack an inferential analysis on the sample data.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The different levels of economic development and different household structures in different regions often cause very different travel behavior [26,27]. In addition, most of the above studies are only a descriptive analysis and lack an inferential analysis on the sample data.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Increasing human demand for natural and land resources has put great pressure on the natural environment [44] from facility construction, landscape alteration, urban development and land reclamation [45,46]. This has led to global land-use change, reduction in vegetation coverage, and growth in built-up areas [47].…”
Section: Input Variablesmentioning
confidence: 99%
“…Indeed, it has been shown that CA models, especially GIS-based CA models, can efficiently simulate urban growth processes [16,34,35,36] and estimate spatial patterns of urban growth [36]. However, calibrating an urban CA is challenging and complicated because of the existing spatial heterogeneity of urban forms and the nonlinearity of urban growth driving forces (cf.…”
Section: Introductionmentioning
confidence: 99%
“…[37,38]). To calibrate urban CA models, some researchers (e.g., [21,30,35,39]) have used statistical approaches, such as multi-criteria evaluation (MCE) or logistic regression (LR), to estimate growth parameters, with moderate success. Fuzzy logic approaches have also been employed to estimate CA parameters; some have even used fuzzy logic to quantify uncertainties in CA models [3,40,41].…”
Section: Introductionmentioning
confidence: 99%